Comparison of Low-Level and High-Intensity Laser Therapy Effects on Functional Outcomes in Knee Osteoarthritis - Fauzan Ahmad; Mohammad Barlian Nugroho; Djoko Witjaksono; Viera Wardhani (Glosains: Jurnal Sains Global Indonesia, 2026)
Background: Low-Level Laser Therapy (LLLT) and High-Intensity Laser Therapy (HILT) are widely used nonpharmacological interventions for patients with knee osteoarthritis (KOA). However, scientific evidence comparing the effectiveness of these two therapies on functional outcomes remains limited. Objective: To compare the effects of LLLT and HILT combined with quadriceps bench exercises on knee function, walking speed, and knee proprioception in patients with KOA. Methods: This randomized controlled trial used a pretest–posttest design at Dr. Saiful Anwar Regional General Hospital, Malang. Patients with KOA were randomly assigned to LLLT or HILT groups, with both receiving quadriceps exercises for four weeks. Knee function, walking speed, and proprioception were assessed using KOS-ADLS, 10MWT, and joint position sense tests. Pre- and post-intervention changes were statistically compared within and between groups. Results: Both LLLT and HILT produced significant improvements in functional outcomes after four weeks of intervention. Improvements in knee function were observed in both groups, with no significant between-group difference. Walking speed increased significantly in both groups; however, the LLLT group demonstrated a significantly greater improvement than the HILT group (p = 0.030). Regarding proprioception, a significant improvement was observed only in the LLLT group, although no significant between-group difference was found following the intervention. Conclusion: The findings suggest that LLLT may be considered an effective noninvasive adjunctive therapy for improving mobility in patients with KOA.